2011
DOI: 10.1111/j.1601-6343.2011.01525.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of volumetric measurement of teeth in vivo based on cone beam computer tomography

Abstract: The accuracy of the CBCT method for volumetric measurement of teeth in vivo is comparable to the Micro-CT method in vitro. The CBCT method has the potential possibility to be applied in studies on root resorption associated with orthodontic force. Further study is needed to prove the sensitivity of the method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 26 publications
1
45
0
1
Order By: Relevance
“…Many studies have concluded that volumetric measurement of teeth using CBCT is a reliable, reproducible, and valid method. [16][17][18] As of today, there has been only one study evaluating root resorption after RME with CBCT in vivo. 5 The volumetric data set comprises isotropic structures, known as voxels, each representing a specific degree of X-ray absorption.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have concluded that volumetric measurement of teeth using CBCT is a reliable, reproducible, and valid method. [16][17][18] As of today, there has been only one study evaluating root resorption after RME with CBCT in vivo. 5 The volumetric data set comprises isotropic structures, known as voxels, each representing a specific degree of X-ray absorption.…”
Section: Resultsmentioning
confidence: 99%
“…used for each tooth before expansion, after expansion, and after 6 months of retention. 18 Tooth volume loss and its percentage were measured. The percentage of root volume loss was calculated by subtracting the postexpansion root volume from the preexpansion volume.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study that has evaluated volumetric computations of alveolar clefts derived from virtual 3D or 3D printed models using CBCT. Several non-cleft studies have evaluated the dimensional accuracy of CBCT scanning compared to micro-CT imaging finding virtual 3D models derived from CBCT scans are accurate for volumetric calculation of teeth 19 and bovine bone cavities. 20 Our results are in line with these and are comparable to other investigations of the dimensional accuracy of CAD models produced from either CT or CBCT scans.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Wang et al 38 studied in vivo the accuracy of volumetric measurements of the cone beam on a sampling of 27 maxillary and mandibular premolars. The authors conclude that the use of CBCT in the detection of orthodontically induced root resorption is an obvious possibility.…”
Section: How To Detect Oiirr: Input From the Cone Beammentioning
confidence: 99%